Prevalence of Early Marriage among the Mushar (Musahar) Community of Nepal — A Review - Adhikari, Anjali (NPRC Journal of Multidisciplinary Research, 2025)
Background: Child marriage is a persistent public health and human rights issue in Nepal, disproportionately affecting marginalized communities. The Musahar (Mushar), a Dalit group in the Terai region, experience extreme socioeconomic deprivation and social exclusion, which are known drivers of early marriage. However, national health surveys often lack the disaggregated data needed to understand the specific burden within this vulnerable population.Objective: This review aimed to synthesize existing evidence on early marriage in Nepal, with a specific focus on compiling Musahar-specific prevalence, drivers, and consequences, and to identify critical research gaps to inform future targeted interventions.Methods: A narrative review was conducted, synthesizing evidence from international and national agency reports (e.g., UNICEF, UNFPA), peer-reviewed literature from databases including NepJOL, NGO project reports, and recent media/advocacy documents. The search strategy prioritized finding both quantitative and qualitative sources to triangulate evidence on the Musahar community.Findings: National data indicate that 33-40% of Nepali women aged 20-24 were married before 18, with higher rates in the Terai. While direct, representative data for the Musahar are absent, consistent qualitative and programmatic evidence reveals an alarmingly high prevalence, with accounts of marriages occurring as young as 10-11 years. Key drivers include extreme poverty, debt, severe gender disparities in education, caste-based exclusion, and restrictive social norms. Consequences are severe, encompassing school dropout, early pregnancy, poor health outcomes, and intergenerational poverty.Conclusion: Early marriage is a pervasive and severe issue within the Musahar community, intensified by their profound marginalization. A significant evidence gap exists due to the lack of representative, caste-disaggregated quantitative data on marriage prevalence and a paucity of rigorously evaluated interventions tailored to this group.Implication: There is an urgent need for future research to generate robust, representative estimates of early marriage prevalence among Musahar girls and to identify community-specific drivers through mixed-methods studies. This evidence is crucial for policymakers and program implementers to design effective, equitable, and targeted interventions to prevent child marriage and ensure Nepal's most marginalized are not left behind.